2013
DOI: 10.1371/journal.pone.0079689
|View full text |Cite
|
Sign up to set email alerts
|

GTP Hydrolysis of TC10 Promotes Neurite Outgrowth through Exocytic Fusion of Rab11- and L1-Containing Vesicles by Releasing Exocyst Component Exo70

Abstract: The use of exocytosis for membrane expansion at nerve growth cones is critical for neurite outgrowth. TC10 is a Rho family GTPase that is essential for specific types of vesicular trafficking to the plasma membrane. Recent studies have shown that TC10 and its effector Exo70, a component of the exocyst tethering complex, contribute to neurite outgrowth. However, the molecular mechanisms of the neuritogenesis-promoting functions of TC10 remain to be established. Here, we propose that GTP hydrolysis of vesicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 66 publications
10
69
2
Order By: Relevance
“…Overexpression of the Exo70 subunit can induce filopodia and increase secretion (Gupton and Gertler, 2010; Wang et al, 2004). In embryonic mouse cortical neurons, Exo70 overexpression promotes neuritogenesis, supporting an important role for exocytosis and the exocyst complex in developing neurons (Fujita et al, 2013; Gupton and Gertler, 2010; Vega and Hsu, 2001). Several groups have shown various exocyst components at the tips of extending neurites, further supporting their role in neuritogenesis and neurite extension (Hazuka et al, 1999; Lalli and Hall, 2005; Mehta et al, 2005).…”
Section: Exocytosismentioning
confidence: 84%
See 1 more Smart Citation
“…Overexpression of the Exo70 subunit can induce filopodia and increase secretion (Gupton and Gertler, 2010; Wang et al, 2004). In embryonic mouse cortical neurons, Exo70 overexpression promotes neuritogenesis, supporting an important role for exocytosis and the exocyst complex in developing neurons (Fujita et al, 2013; Gupton and Gertler, 2010; Vega and Hsu, 2001). Several groups have shown various exocyst components at the tips of extending neurites, further supporting their role in neuritogenesis and neurite extension (Hazuka et al, 1999; Lalli and Hall, 2005; Mehta et al, 2005).…”
Section: Exocytosismentioning
confidence: 84%
“…Expression levels of the exocyst subunit Sec6 correlate temporally with the occurrence of neuritogenesis (Chin et al, 2000). During axon specification, the exocyst complex is integral in both vesicle targeting to the axon (Fujita et al, 2013) and the regulation of cell polarity (He and Guo, 2009). Lalli reported that siRNA depletion of exocyst subunits Sec6, Sec8, or Exo84 inhibits axon specification in rat cortical neurons, as no neurites become positive for the axon marker tau.…”
Section: Exocytosismentioning
confidence: 99%
“…Dlc1 can act as a GTPase activating protein (GAP) for several Rho GTPases including CDC42 and Rho A–C which have been implicated in cytoskeleton regulation [48]. Furthermore, the Rho GTPase Rhoq promotes neurite outgrowth through a Rab11 and Exo70 dependent mechanism [49]. Therefore, repression of Rhoq and Dlc1 expression by Rem2 signaling could represent another mechanism by which Rem2 restricts dendritic complexity.…”
Section: Resultsmentioning
confidence: 99%
“…T he EXO70 (exocyst component of 70 kDa) protein is a component of the evolutionarily conserved octameric exocyst complex that tethers post-Golgi vesicles to the plasma membrane before SNARE-mediated membrane fusion (1). As an important component of the exocyst complex that mediates exocytosis, EXO70 regulates, for example, neurite outgrowth, epithelial cell polarity establishment, cell motility, and cell morphogenesis in animal cells (2)(3)(4)(5)(6). In plants, EXO70 proteins participate in polarized pollen tube growth, root hair growth, deposition of cell wall material, cell plate initiation and maturation, defense, and autophagy (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%